Look at the problem of socialization through the prism of self-actualization in humanistic psychology - Cherniak, A. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article deals with communication features of self-actualization and socialization in humanistic psychology.